Can legal weed win?: the blunt realities of cannabis economics - Goldstein, Robin (University of California Press, 2022)
We call it weed -- Legal vs. illegal : a market battle -- Prices get high -- We ask our data : where's the cheapest legal weed? -- California dreamin' -- Sabrina's story -- Legal weed in 2025 -- How to survive legalization -- Conclusion : five pipe dreams about legal weed.